Network over‐connectivity differentiates autism spectrum disorder from other developmental disorders in toddlers: A diffusion MRI study. Issue 5 (17th January 2017) - Conti, E.; Mitra, J.; Calderoni, S.; Pannek, K.; Shen, K. K.; Pagnozzi, A.; Rose, S.; Mazzotti, S.; Scelfo, D.; Tosetti, M.; Muratori, F.; Cioni, G.; et al.
Abstract: Advanced connectivity studies in toddlers with Autism Spectrum Disorder (ASD) are increasing and consistently reporting a disruption of brain connectivity. However, most of these studies compare ASD and typically developing subjects, thus providing little information on the specificity of the abnormalities detected in comparison with other developmental disorders (other‐DD). We recruited subjects aged below 36 months who received a clinical diagnosis of Neurodevelopmental Disorder (32 ASD and 16 other‐DD including intellectual disability and language disorder) according to DSM‐IV TR. Structural and diffusion MRI were acquired to perform whole brain probabilistic and anatomically constrained tractography. Network connectivity matrices were built encoding the number of streamlines (DNUM ) and the tract‐averaged fractional anisotropy (DFA ) values connecting each pair of cortical and subcortical regions. Network Based Statistics (NBS) was finally applied on the connectivity matrices to evaluate the network differences between the ASD and other‐DD groups. The network differences resulted in an over‐connectivity pattern (i.e., higher DNUM and DFA values) in the ASD group with a significance of P  < 0.05. No contra‐comparison results were found. The over‐connectivity pattern in ASD occurred in networks primarily involving the fronto‐temporal nodes, known to be crucial for social‐skill development and basal ganglia, related to restricted and repetitive behaviours in ASD. To our knowledge, this is the first network‐based diffusion study comparing toddlers with ASD and those with other‐DD. Results indicate the detection of different connectivity patterns in ASD and other‐DD at an age when clinical differential diagnosis is often challenging. Hum Brain Mapp 38:2333–2344, 2017 . ©2017 Wiley Periodicals, Inc.